1980
DOI: 10.1159/000176279
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in Premature Infants

Abstract: Premature infants have a lower selenium concentration in serum than full-term infants and children. The selenium concentration goes down quickly in infants treated for respiratory distress syndrome without supplementation. One premature infant with bronchopulmonary dysplasia had persistently low concentrations of selenium. Vitamin E supplements did not affect the serum selenium concentration in healthy premature infants. Supplementation with 3 µg/kg of selenium in parenteral fluids prevented the fall in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
3

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 16 publications
2
25
0
3
Order By: Relevance
“…Selenium deficiency has been linked to a multitude of conditions such as Kashin cardiomyopathy, Kashin-Beck osteoartropathy, systemic immune response syndrome and sepsis in adults, and chronic lung disease and hemolytic anemia in preterm infants. [1][2][3][4][5][6][7] Selenium as selenocysteine is a component of the metalloenzymes that are present in many body tissues, including glutathione peroxidase (GSHPx) and iodothyronine deiodinase type I. [7][8][9] GSHPx serves as an antioxidant, which protects cells from free radical damage.…”
mentioning
confidence: 99%
“…Selenium deficiency has been linked to a multitude of conditions such as Kashin cardiomyopathy, Kashin-Beck osteoartropathy, systemic immune response syndrome and sepsis in adults, and chronic lung disease and hemolytic anemia in preterm infants. [1][2][3][4][5][6][7] Selenium as selenocysteine is a component of the metalloenzymes that are present in many body tissues, including glutathione peroxidase (GSHPx) and iodothyronine deiodinase type I. [7][8][9] GSHPx serves as an antioxidant, which protects cells from free radical damage.…”
mentioning
confidence: 99%
“…Low selenium levels in animals and humans are associated with low glutathione peroxidase activity (9, II), and selenium-deficient animals have increased susceptibility to oxidative lung injury (12). Low blood selenium levels in premature infants have been documented and suggested as a potential risk factor for BPO (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Decrease in selenium concentration was described some decades ago in preterm infants who had respiratory diseases and were receiving parenteral nutrition without selenium supplementation for the first 14 postnatal days, and concentration increased when feeding with selenium-supplemented formula was introduced [19]. Other authors have shown a progressive decline in glutathione peroxidase activity in erythrocyte and plasmatic selenium in preterm newborns from the second postnatal week when they were fed with standard milk formula.…”
Section: Selenium Supplementationmentioning
confidence: 97%